Проблема эффективности государственного контроля - Lopushanskaia D. I., Ivanenko I. N. (Innovative technologies in science and education, 2017)
The article considers the problems of efficiency of state control at the present stage of development of the Russian state
Keywords: государственное управление; государственный контроль; state control